Associations between anxiety and working memory components in clinically evaluated children with and without ADHD - Marsh, Carolyn L.; Gaye, Fatou; Cibrian, Enrique; Cho, Sooyun; Tatsuki, Miho O.; Obi, Julia O.; Geren, Meaghan E.; Harmon, Sherelle L.; Kofler, Michael J. (Frontiers in Psychiatry, 2025)
Theoretical models describe working memory difficulties as risk factors and/or outcomes of anxiety in children, but the current evidence base is surprisingly mixed. Understanding the nature of the working memory/anxiety relation is complicated by the multi-component nature of each of these constructs. Consideration of the co-occurrence of anxiety with attention-deficit/hyperactivity disorder (ADHD) is also imperative given that ADHD is associated with large magnitude working memory impairments. The current study addressed these considerations using bifactor modeling to evaluate associations between latent estimates of working memory and anxiety subcomponents. The carefully-phenotyped sample included N=340 children between the ages of 8 and 13 (M = 10.31, SD = 1.39; 144 female participants), with an oversampling of children with ADHD (n=197). Results showed that domain-general anxiety was associated with worse phonological short-term memory (r = -.22, p = .01), but not central executive working memory or visuospatial short-term memory. Domain-specific anxiety factors (cognitive worry, physiological arousal) did not uniquely predict any of the short-term/working memory components. Further, multigroup analysis indicated that the magnitude and significance of these relations were comparable for both children with and without ADHD. Our findings did not support unique relations between domain-specific cognitive worry/physiological arousal and instead implicated domain-general common anxiety in difficulties with phonological short-term memory. Further research will be needed to replicate findings using this approach across additional measures and performance metrics, while continuing to account for the high co-occurrence between anxiety and ADHD.